Local micro-networks for green transition of the wool supply chain - Rossana Gaddi; Luciana Mastrolonardo (Agathón)
Italy’s inland areas face complex challenges such as depopulation, isolation and economic weakness. Through a research project conducted in Taranta Peligna (Chieti, IT), the paper aims to enhance the wool supply chain by adopting a systemic, co-design and collaborative approach among local governments, institutions and communities. To develop innovative and sustainable solutions, implementing systemic design methodologies and through the analysis of international case studies, concrete actions are proposed, such as creating an energy community and the activation of sustainable washing centres of a Network Observatory. Through a series of strategic interventions, the project aims to re-establish the importance of the wool industry by integrating modern technologies into traditional processes to achieve a revitalised, low-impact local economy.